2015
DOI: 10.1097/id.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions of Undergraduate Dental Students Toward Dental Implants—An All India Survey

Abstract: This study concludes that a revision in the undergraduate dental curriculum is required to make the students better equipped with the technicalities of implant dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 19 publications
2
29
1
1
Order By: Relevance
“…In a similar vein, the study also showed that most patients ignore some very important factors such as the fact that smoking has a negative impact on the life expectancy of the implant (48%), the risk of peri-implantitis (80%), or the fact that they believe that an implant-supported prosthesis has a long life of 20-25 years (52%) ( 11 ). Over 60% of the undergraduates who responded to the present questionnaire believed the life of these treatments is between 10 and 20 years, without significant difference between the groups, in contrast to the study by Chaudhary et al ( 6 ) in which only 39.8% answered the question in this way. Such opinions confirm the need for factual information so that undergraduates and post-graduates may give the patient realistic expectations for treatment, factors involved in the treatment, and about the risks involved in each individual case ( 11 ).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In a similar vein, the study also showed that most patients ignore some very important factors such as the fact that smoking has a negative impact on the life expectancy of the implant (48%), the risk of peri-implantitis (80%), or the fact that they believe that an implant-supported prosthesis has a long life of 20-25 years (52%) ( 11 ). Over 60% of the undergraduates who responded to the present questionnaire believed the life of these treatments is between 10 and 20 years, without significant difference between the groups, in contrast to the study by Chaudhary et al ( 6 ) in which only 39.8% answered the question in this way. Such opinions confirm the need for factual information so that undergraduates and post-graduates may give the patient realistic expectations for treatment, factors involved in the treatment, and about the risks involved in each individual case ( 11 ).…”
Section: Discussioncontrasting
confidence: 86%
“…Data obtained by the present questionnaire, states there was a wide disparity of opinion about general concepts in implant treatments such as: the estimated duration of implant treatment, follow-up requirements, or the most important factor governing the success of implant-based treatments. As the degree course advanced and students progress in their learning, they agreed that implant treatments are less aggressive than dental preparation procedures; this datum (59.8%) coincides with a population of dental undergraduates in India ( 6 ). Interestingly, this is the main reason why patients request this type of treatment, Ken ( 11 ) report that 32% of patients declared this to be the reason for choosing implant-based treatment, being the second reason a rejection of the option of removable prostheses, and the third because the treatment had been recommended by someone they knew.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies in Europe and Australia show that, with the integration of implant dentistry in daily dental practice [20,21], more universities are including oral implant-related education in their undergraduate courses. Another study in India shows that 91.7% of students are eager to learn more about oral implants in college courses [22]. Thus, implant dentistry is slowly become a necessary part of pre-clinical teaching in dental education.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Europe and Australia showed that, with the integration of implant dentistry in daily dental practice [12,13], more universities were including oral implant-related education in their undergraduate courses. Another study in India shows that 91.7% of students are eager to learn more about oral implants in college courses [14].…”
Section: Introductionmentioning
confidence: 99%